Simplified antibiotic regimens compared with injectable procaine benzylpenicillin plus gentamicin for treatment of neonates and young infants with clinical signs of possible serious bacterial infection when referral is not possible: a randomised, open-label, equivalence trial. Issue 9979 (2nd May 2015) - Tshefu, Antoinette; Lokangaka, Adrien; Ngaima, Serge; Engmann, Cyril; Esamai, Fabian; Gisore, Peter; Ayede, Adejumoke Idowu; Falade, Adegoke Gbadegesin; Adejuyigbe, Ebunoluwa A; Anyabolu, Chineme Henry; Wammanda, Robinson D; Ejembi, Clara L; et al.
Summary: Background: WHO recommends hospital-based treatment for young infants aged 0–59 days with clinical signs of possible serious bacterial infection, but most families in resource-poor settings cannot accept referral. We aimed to assess whether use of simplified antibiotic regimens to treat young infants with clinical signs of severe infection was as efficacious as an injectable procaine benzylpenicillin–gentamicin combination for 7 days for situations in which hospital referral was not possible. Methods: In a multisite open-label equivalence trial in DR Congo, Kenya, and Nigeria, community health workers visited all newborn babies at home, identifying and referring unwell young infants to a study nurse. We stratified young infants with clinical signs of severe infection whose parents did not accept referral to hospital by age (0–6 days and 7–59 days), and randomly assigned each individual within these strata to receive one of the four treatment regimens. Randomisation was stratified by age group of infants. An age-stratified randomisation scheme with block size of eight was computer-generated off-site at WHO. The outcome assessor was masked. We randomly allocated infants to receive injectable procaine benzylpenicillin–gentamicin for 7 days (group A, reference group); injectable gentamicin and oral amoxicillin for 7 days (group B); injectable procaine benzylpenicillin–gentamicin for 2 days, then oral amoxicillin for 5 days (group C); or injectable gentamicin for 2 days and oral amoxicillin for 7 days (group D). Trained health professionals gave daily injections and the first dose of oral amoxicillin. Our primary outcome was treatment failure by day 8 after enrolment, defined as clinical deterioration, development of a serious adverse event (including death), no improvement by day 4, or not cured by day 8. Independent outcome assessors, who did not know the infant's treatment regimen, assessed study outcomes on days 4, 8, 11, and 15. Primary analysis was per protocol. We used a prespecified similarity margin of 5% to assess equivalence between regimens. This study is registered with the Australian New Zealand Clinical Trials Registry, number ACTRN12610000286044. Findings: In Kenya and Nigeria, we started enrolment on April 4, 2011, and we enrolled the necessary number of young infants aged 7 days or older from Oct 17, 2011, to April 30, 2012. At these sites, we continued to enrol infants younger than 7 days until March 29, 2013. In DR Congo, we started enrolment on Sept 17, 2012, and continued until June 28, 2013. We randomly assigned 3564 young infants to either group A (n=894), group B (n=884), group C (n=896), or group D (n=890). We excluded 200 randomly assigned infants, who did not fulfil the predefined criteria of adherence to treatment and adequate follow-up. In the per-protocol analysis, 828 infants were included in group A, 826 in group B, 862 in group C, and 848 in group D. 67 (8%) infants failed treatment in group A compared with 51 (6%) infants in group B (risk difference −1·9%, 95% CI −4·4 to 0·1), 65 (8%) in group C (−0·6%, −3·1 to 2·0), and 46 (5%) in group D (−2·7%, −5·1 to 0·3). Treatment failure in groups B, C, and D was within the similarity margin compared with group A. During the 15 days after random allocation, 12 (1%) infants died in group A, compared with ten (1%) infants in group B, 20 (2%) infants in group C, and 11 (1%) infants in group D. An infant in group A had a serious adverse event other than death (injection abscess). Interpretation: The three simplified regimens were as effective as injectable procaine benzylpenicillin–gentamicin for 7 days on an outpatient basis in young infants with clinical signs of severe infection, without signs of critical illness, and whose caregivers did not accept referral for hospital admission. Funding: Bill & Melinda Gates Foundation grant to WHO.